Commercial Sports Facilities in Big Cities: A Case Study - Nahid, Mehzabul Hoque; Abrar, Araf (Indonesian Journal of Sport Management, 2023)
This study aims to explore the issues of commercial sports facilities in the metropolitan regions of Dhaka City and examine the determinants that influence their use and effectiveness. In densely populated urban areas such as Dhaka, there needs to be more academic research on the usage and issues with limited sports facilities. This research constitutes the initial attempt to identify the challenges key stakeholders face in commercial sports facilities located in Dhaka. The present investigation utilizes a qualitative case study approach, employing semi-structured interviews to collect data from a sample of seventeen individuals who demonstrate a strong inclination towards sports or have availed themselves of sports facilities situated within the geographic limits of Dhaka Metro. The study employed convenience and purposive sampling techniques for participant selection. It utilized inductive analysis for objectively analyzing the data, enabling the identification of themes and patterns without any predetermined theoretical frameworks being imposed on the data. ATLAS.ti is a software used in this study to analyze data thematically. The findings of this study contribute to an improved understanding of the perspectives held by key stakeholders regarding the operation of commercial sports facilities in urban areas with high population densities.